Interactive Simulators for Steel Industry Safety Training. Issue 4 (18th March 2019) - Moreland, John; Toth, Kyle; Fang, Yuqian; Block, Michelle; Page, Garrett; Crites, Shawn; Zhou, Chenn Q.
Abstract : This paper describes a method for the creation of interactive software for safety training, with a focus on life‐threatening situations encountered in the steel industry. This approach uses tools from the gaming industry to create photorealistic three‐dimensional models and interactive situations that are typically encountered in steel production settings. Users interact with the models in real time through scripted scenarios in which they must carry out work‐related tasks that require understanding and application of safety concepts. An example scenario that focuses on work at height and fall protection is discussed along with practical considerations for implementation. Abstract : Tools developed for the gaming industry is be used for training. Photorealistic three‐dimensional models combined with meaningful choices and narrative provide a mechanism to engage learners. This paper describes a method of creating interactive scenarios for safety training in the steel industry. An example involving fall protection is discussed along with methods of implementation.